2019
DOI: 10.1161/jaha.118.009585
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Calcium and Insulin Resistance With Hypertension Risk: A Prospective Population‐Based Study

Abstract: Background The temporal sequence between serum calcium and insulin resistance (IR) and their effects on hypertension are unclear. We studied the association between serum calcium and IR, with risk of hypertension events in a longitudinal cohort conducted in China. Methods and Results Data from 8653 subjects aged 20 to 74 years with an average follow‐up of 5.3 years were analyzed. Serum calcium, and fasting and 2‐hour serum glucose and insulin were measured at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The relationship between arterial blood pressure and IR has been shown in many studies 42,43 In our study, we found that systolic blood pressure is an independent predictor of IR. This may be due to increased fat tissue in the body that plays an important role in IR and subclinical inflammation caused by inflammatory cytokines, such as IL-6, IL-1 and TFN-alpha secreted from this adipose tissue.…”
Section: Discussionsupporting
confidence: 71%
“…The relationship between arterial blood pressure and IR has been shown in many studies 42,43 In our study, we found that systolic blood pressure is an independent predictor of IR. This may be due to increased fat tissue in the body that plays an important role in IR and subclinical inflammation caused by inflammatory cytokines, such as IL-6, IL-1 and TFN-alpha secreted from this adipose tissue.…”
Section: Discussionsupporting
confidence: 71%
“…The benefits of L-carnitine supplementation in terms of BP levels are in part due to improved insulin sensitivity and glucose control [23]. Hyperinsulinemia and insulin resistance are risk factors for increased BP [24,25]. According to the "energy starvation" hypothesis, carnitine can improve cardiomyocytes' energy metabolism, thereby improving the mechanical efficiency and function of cardiac fibroblasts and regulating BP [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an association with the development and progression of diabetes is obvious. Furthermore, deregulated Ca 2+ signaling has been associated with the development of one of the key characteristics of T2DM i.e., insulin resistance [141][142][143]. Deregulated Ca 2+ homeostasis has been implicated in a vast range of disease conditions.…”
Section: Ca 2+ In the Development Of T2dmmentioning
confidence: 99%